(3GdEeJGY HCMcGe GdEbWGYs - (3jOcGQ Hf CMeO Hf jhSa GdGhRGfs
(3ChdgG (B:s
(3hHYO ajbhd bO WdH efi HYV abgGA HdOfG s
(3BNQgG (B:s
(3hbO VefJg eSGFd dGJhLO EdG ajg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(D 13) s
Keywords: (3CUhd Gdabgs